Diversity of the Peruvian Andean maize (Zea mays L.) race Cabanita: Polyphenols, carotenoids, in vitro antioxidant capacity, and physical characteristics - Fuentes-Cardenas, Iraida Sara; Cuba-Puma, Rody; Marcilla-Truyenque, Shaneri; Begazo-Gutiérrez, Huber; Zolla, Gastón; Fuentealba, Claudia; Shetty, Kalidas; Ranilla, Lena Gálvez (Frontiers in Nutrition, 2022)
The high diversity of the Peruvian Andean maize (Zea mays L.) represents a biological and genetic heritage relevant for food security, but few studies are targeted towards its characterization and consequent valorization and preservation. The objective of this study was to evaluate the potential of the Peruvian Andean maize race Cabanita with respect to its bioactive profiles (free and bound phenolic and carotenoid composition), physical characteristics, and in vitro antioxidant properties. Maize landraces with variable kernel pigmentation were collected from two provinces (Caylloma and Castilla) within the Arequipa region (among ten Andean sites) and the phytochemical profile was evaluated by Ultra High-Performance Liquid Chromatography with diode array detector (UHPLC-DAD). All maize samples were important sources of phenolic compounds mainly soluble p-coumaric and ferulic acid derivatives whereas anthocyanins were only detected in maize with partially red pigmented kernels. Major phenolic compounds in the bound phenolic fractions were ferulic acid and its derivatives along with p-coumaric acid. Carotenoid compounds including xanthophylls such as lutein, lutein isomers, and zeaxanthin were only detected in orange and white-yellow pigmented maize and are reported for the first time in Peruvian landraces. The multivariate analysis using Principal Components Analysis (PCA) revealed low variability of all data which may indicate a level of similarity among maize samples based on evaluated variables. However, maize grown in Caylloma province showed more homogeneous physical characteristics and higher yield, whereas higher phenolic contents and antioxidant capacity were observed in maize from Castilla. Samples CAY (yellow-pigmented kernel, Castilla) and COM (orange-pigmented kernel, Caylloma) had the highest total phenolic (246.7 mg/100 g dried weight basis, DW) and carotenoid (1.95 µg/g DW) contents among all samples. The variable Andean environmental conditions along with differences in farming practices may play a role and should be confirmed with further studies. Current results provide the metabolomic basis for future research using integrated omics platforms targeted towards the complete characterization of the ethnic-relevant maize race Cabanita.